Mapping Transition Metal–Nitrogen–Carbon Catalyst Performance on the Critical Descriptor Diagram - Zagal-Moya, J; Zagal-Moya, J (Elsevier B.V., 2021)
Platinum group metal–free electrocatalysts and in particular transition metal–nitrogen–carbon catalysts are becoming interesting candidates as cheap alternatives to Pt-based catalysts for the oxygen reduction reaction in polymer electrolyte fuel cells. Unified activity-stability correlations are needed to provide practical guidelines for a rational catalyst design. A discussion of different characterization techniques for studying possible activity descriptors is presented, with a specific focus on active site density and turnover frequency. These descriptors will be associated to the morphology of the various transition metal–nitrogen–carbon electrocatalysts investigated in the recent literature. The underlined correlation for this class of platinum group metal–free electrocatalysts offers important insights required for the development of the next generation of catalytic materials with enhanced stability that can solve the main activity and durability barriers needed for the replacement of Pt-based counterparts. © 2021 Elsevier B.V.